TEKNIK PENELITIAN KUALITATIF - Fitri Nurpita; Mely Cahyani; Zamsiswaya; Luthfi Anshori Rahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Qualitative research plays a crucial role in social science and educational studies because it can deeply explore meaning, experiences, and social realities. However, students and novice researchers still lack understanding of the techniques used in qualitative research. Therefore, this study aims to systematically describe and explain various qualitative research techniques. This study employed a qualitative approach with a library research approach. Data were obtained from research methodology books, journal articles, and other scientific literature relevant to the research. Data collection was conducted through document search and analysis, while data analysis employed descriptive qualitative techniques. The results indicate that qualitative research techniques include the selection of data sources and types, the role of the researcher as the primary instrument, observation, in-depth interviews, field notes, the use of documents, and sampling techniques such as purposive, snowball, and maximum variation sampling. A good understanding of these techniques can help researchers conduct qualitative research in a more focused and systematic manner, producing meaningful findings.